Acute eosinophilic pneumonia as a complication of influenza A (H1N1) pulmonary infection - Larranaga, Jose Maria; Marcos, Pedro J; Pombo, Francisco; Otero-Gonzalez, Isabel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Acute eosinophilic pneumonia (AEP) is a rare disease characterized by its acute onset and a clinical presentation simulating a bacterial pneumonia. Although it can be idiopathic, it has been described related to drugs, toxic agents and infections, mostly parasitic. We describe the case of influenza A (H1N1) severe pneumonia complicated by an acute eosinophilic pneumonia. Patient presented with respiratory failure and diffuse ground-glass opacities at chest-computed tomography. Clinical suspicion for this complication and bronchoalveolar lavage with cellular count analysis is crucial.